T3 Severe hypoxia exists within pulmonary tuberculosis lesions and augments matrix metalloproteinase-mediated immunopathology. (14th November 2013) - Belton, M; Brilha, S; Fryer, T; Hong, Y; Mauri, F; Patel, N; Tezera, L; Nijran, K; Elkington, PT; Friedland, JS
Abstract : Introduction: Mycobacterium tuberculosis (MTb) causes approximately two million deaths each year. Extensive lung destruction is a hallmark of pulmonary tuberculosis and is caused by the breakdown of lung extracellular matrix by host matrix metalloproteinases (MMPs). Hypoxia upregulates gene expression and secretion of many inflammatory mediators via hypoxia-inducible factor (HIF-1α). Hypoxia has been demonstrated in several animal models of TB infection but no studies have been performed to investigate hypoxia in humans. Methods: To investigate the presence of hypoxia in human M.tb infection we performed PET-CT scanning using the hypoxia tracer [18F]FMISO in patients with pulmonary infection. Next, primary human monocyte-derived macrophages (MDMs) and human respiratory epithelial cells were stimulated by M.tb H37RV or conditioned media from Mtb-infected monocytes (CoMTb) in a specially commissioned hypoxia workstation at 1% O2, 5% CO2. MMPs and their specific inhibitors (TIMP-1/2) were analysed by ELISA, Luminex array, zymography and confocal microscopy. Gene expression was analysed by qPCR and promoter activity by dual luciferase activity. Total HIF-1α was measured by western analysis. The effect of HIF-1α blockade was investigated using HIF-1a siRNA. Results: PET-CT scans demonstrated evidence of tracer trapping in regions of consolidation and in regions surrounding pulmonary cavities indicating severe hypoxia. Hypoxia potently upregulated MMP-1 in M.tb -stimulated primary MDMs and MMP-1 and MMP-9 in respiratory epithelial cells compared to normoxia (p < 0.001). Similarly, hypoxia increased MMP-1 gene expression -2500 fold and potently increased MMP-1 promoter activity (p < 0.001). Site-directed mutagenesis of the NFκB binding site in the MMP-1 promoter and SC514 and helenalin chemical inhibition demonstrated that increased MMP-1 activity in hypoxia was regulated via an NFκB dependent mechanism. M.tb infection caused stabilisation of HIF-1α protein even under conditions of normoxia but was more pronounced in hypoxia. Immunohistochemistry of patient samples demonstrated strong HIF-1α immunoreactivity in tuberculosis patients compared to controls. HIF-1α siRNA confirmed that increased MMP-1 activity in hypoxia occurred by a HIF-1α-dependent mechanism. Conclusion: We demonstrate for the first time that severe hypoxia develops within pulmonary TB lesions. Hypoxia increases M.tb -driven MMP-1/9 gene expression and secretion in a HIF-1a-dependent manner. These results support the hypothesis that during Tb infection, hypoxia develops and promotes immunopathology.